Pengaruh Good Governance Dan Komitmen Organisasi Terhadap Kinerja Dinas Pemerintah (Sensus pada Dinas Kota Tasikmalaya) - Monika Sutarsa (LPPM POLITEKNIK LP3I BANDUNG, 2023)
The object of research in this paper is Good Governance, organizational commitment and performance of government agencies. As for the title taken by the author in this thesis is the Influence of Good Governance and Organizational Commitment to Government Service Performance (Census on the Tasikmalaya City Service). The purpose of this study is to find out and analyze the influence of Good Governance and Organizational Commitment on Government Service Performance. In this study the author uses the research method used is descriptive method and causality method. The analytical tool used is Path Analysis. Based on the results of the study it is known that partially Good Governance has a significant positive effect on the performance of the Tasikmalaya City government service, while the organizational commitment does not have a significant effect on the performance of the Tasikmalaya City government service. Simultaneously Good Governance and Organizational Commitment have a significant effect on the performance of the Tasikmalaya City government service.